STUDI DESKRIPTIF MENGENAI PRASARANA OLAHRAGA DALAM MENDUKUNG PRESTASI KABUPATEN LAMPUNG BARAT PADA PEKAN OLAHRAGA PROVINSI LAMPUNG - M. Farhan Rizki Pratama; Fransiskus Nurseto; Muhammad Fajri Rifaldo; Dwi Priyono (STKIP Subang, 2026)
This study aimed to determine the condition of sports infrastructure and its relationship with the sports achievements of West Lampung Regency in the Lampung Provincial Sports Week (PORPROV Lampung). This research was motivated by the importance of sports infrastructure in supporting athlete development and improving regional sports achievements. The research used a descriptive method with a qualitative approach. Data collection techniques were carried out through field observations, interviews with the management of the Indonesian National Sports Committee (KONI) of West Lampung Regency, and documentation related to sports facilities and regional sports achievement data. The collected data were analyzed descriptively to describe the condition of sports infrastructure and its relationship to athlete development and achievements. The results showed that the sports infrastructure in West Lampung Regency consists of a sports stadium and the Aji Saka Sports Hall (GOR), which are used for various sports activities. Several sports facilities were found to be in fairly good condition and could be utilized for athlete training and community sports activities. However, there were still several limitations, such as the athletic track not yet using a synthetic surface, the absence of a permanent throwing area for athletics, limited sports facilities meeting national standards, and uneven distribution of sports facilities. Based on documentation data from KONI West Lampung Regency, during the 2022 Lampung PORPROV, West Lampung Regency obtained a total of 146 medals consisting of 45 gold medals, 32 silver medals, and 69 bronze medals. The analysis results indicated that sports infrastructure has a relationship with the athlete development process and regional sports achievements. The availability of adequate sports facilities can improve training effectiveness and support the enhancement of athlete performance. The conclusion of this study shows that sports infrastructure is one of the important factors in supporting athlete development and regional sports achievements. Therefore, improving the quality, completeness, and distribution of sports infrastructure needs to be carried out continuously to support the improvement of sports achievements in West Lampung Regency in the future.